Chapter Semiconductor Optical Amplifier (SOA)-Based Amplification of Intensity-Modulated Optical Pulses - Deterministic Timing Jitter and Pulse Peak Power Equalization Analysis - Alexoudi, T. (InTechOpen, 2015)
This chapter presents the fate of the charge carriers from the moment of its photogeneration in the perovskite to injection and transport into electrodes. Time-resolved electrical measurement techniques, terahertz (THz) spectroscopy and microwave (MW) conductivity, are primarily used to deconvolute ultrafast processes and to directly access behavior of charged species from the ps to µs timescales. Transient absorption and photoluminescence spectroscopy were also utilized to gain insight on carrier population dynamics and radiatively recombining charges. Photogenerated charged species were converted into highly mobile charges (µe = 12.5 cm2V-1s-1 and µh = 7.5 cm2V-1s-1) almost instantaneously (< 0.2 ps), while the remaining loosely bounded excitons dissociate into mobile charges after 2-3 ps. This high mobility is maintained for at least 1 ns as obtained by THz spectroscopy, while its lifetime is at least few tens of µs as measured by the MW conductivity technique. Lowering the temperature increases carrier mobilities with T-1.6.Dependence and a 75 meV barrier energy is required for temperature-activated recombination. Finally, injection of hole from MAPbI3 to Spiro-OMeTAD was found to be ultrafast and the state and population of dark holes dictate its recombination.